Studi Meta-Analisis Model Pembelajaran Kooperatif tipe Teams Games Tournament (TGT) dalam Pembelajaran Fisika - Nabeela Rahma Noor Aziz; Dasmo Dasmo; Asep Setiadi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
This study aims to analyze the effect of the TGT type of cooperative learning model in learning physics through the overall size, based on education level, by region and dependent variables. This study uses a descriptive method with a meta-analysis approach to the results of scientific research published nationally. There are 8 national journals that fall into the research category. The results showed that learning as a whole with the application of the TGT cooperative learning model was able to improve student learning outcomes with an effect size of 0.459 from the control group. Based on the level of education, it can improve student learning outcomes with an effect size of 0.352 for junior high school education and 0.524 for high school education. Based on region, several regions in Indonesia, namely the island of Java, obtained results with an effect size of 0.743 and Sumatra with 0.419. And based on the dependent variable, the TGT cooperative learning relationship with learning outcomes has an effect size of 0.453; learning achievement has an effect size of 0.743; and understanding the concept has an effect size of 0.335. The three results of this study indicate the magnitude of the influence of the TGT type of cooperative learning model in learning physics. This shows that the TGT type of cooperative learning model is effectively used and has a major influence on learning physics.